From 'Sleeping Giant' to Left–Right Politicization? National Party Competition on the EU and the Euro Crisis. (5th August 2014) - Miklin, Eric
Abstract While European issues have, for a long time, played hardly any role in national elections and party politics, the EU has seen a continuous increase in politicization throughout the last decades. So far, however, contestation has been restricted largely to constitutional issues, and has been driven mainly by Eurosceptic parties that challenged mainstream parties' positive attitudes towards EU integration. This article discusses to what extent the euro crisis has added to this a left‐right conflict between mainstream parties about their different views on European policies. It argues that the potential for such debates across the EU remains restricted. While the euro crisis has clearly increased the saliency of European issues, overall the incentive structure of mainstream parties in many Member States still works against publicly visible discussions among them. The plausibility of the argument is demonstrated through a comparison of interparty debates on the euro crisis in Austria and Germany.